Study of salivary electrolyte in type 2 diabetes mellitus patients of North Gujarat region of India - Thakkar, Jiger M.; Patel, Dinesh C. (International Journal of Research in Medical Sciences, 2022)
Background: A lack of literature on the probable relationship between diabetes and salivary electrolyte. Therefore, present study aims to study of salivary electrolyte in type 2 diabetes mellitus patients of North Gujarat region of India. Methods: The present cross sectional study was done on 60 subjects of diabetes mellitus (T2DM) and 60 subjects’ non-diabetic healthy controls at Banas medical college and our hospital. The subject’s demographic and anthropometric parameters were recorded; detailed history and clinical examination were performed in the entire cases. The saliva was collected in the fasting state during resting state. Salivary pH, flow rate, biochemical variables and electrolytes were analyzed. Data which was collected was statistically analyzed. Results: Predominance of the T2DM subjects was in the age group of 41-45 years. Mean value for age (p<0.05), body mass index (p<0.01), waist- hip ratio (p<0.05), salivary Potassium (p<0.001), glucose (p<0.001), Chloride (p<0.01), bicarbonates (p<0.01) and sodium levels (p<0.001) were significantly higher in the T2DM subjects where as salivary pH (p<0.01), flow rate (p<0.01) and calcium level (p<0.001) were significantly lower in the T2DM subjects. Conclusions: In our study, we conclude that significant variations were reported in salivary pH, flow rate and electrolyte variables between diabetics and non diabetics. Therefore, we suggested that estimation of salivary variables might be a cost effective and a non invasive choice for screening, diagnosis and monitoring of diabetes instead of blood.